Prevalence of QT interval prolongation in inflammatory bowel disease - Pattanshetty, Deepak J.; Gajulapalli, Rama Dilip; Anna, Kiran; Biyyani, Raja Shekhar Sappati (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: There is growing evidence linking various cardiac complications with inflammatory bowel disease (IBD). Electrolyte abnormalities, chronic inflammation, and medication use (such as Infliximab) that are associated with IBD are all independent risk factors for QT interval prolongation. Given that malignant ventricular arrhythmias are associated with QT interval prolongation, it is important to risk stratify this subset of patients. Our objective was to evaluate the prevalence of abnormal QT interval prolongation (defined by a QT interval of >450 ms in men and >460 ms in women) in an IBD population. Materials and Methods: A retrospective chart review of patients with IBD from the Metro Hospital database was performed. Patients’ demographic characteristics and laboratory data were abstracted. “RR” and “QT” intervals were measured from the last available electrocardiogram, and corrected QT (QTc) interval was calculated from lead II using Bazett’s formula. Results: Of 142 eligible patients, 42.3% (n=22/52) of males and 48.9% (n=44/90) of females had a prolonged QTc interval. Patients with IBD having a prolonged QTc interval had a higher body mass index than those with a normal QTc interval (29.7±6.9 vs. 26.2±5.9, p=0.005). Conclusion: Our study demonstrates that patients with IBD are at a higher risk of developing QTc interval prolongation.